Evaluasi Peraturan Dusun Nomor 03 Tahun 2020 Tentang Larangan Membuka Aurat/Wajib Berhijab (Studi Kasus: Dusun Baru Pusat Jalo Kecamatan Muko Muko Bathin VII Kabupaten Bungo) - Harpisyah Harpisyah; Umi Kalsum (Universitas Muara Bungo, 2023)
This research is entitled, Evaluation of Hamlet Regulation Number 03 of 2020 concerning Prohibition of Revealing the Private Parts/Compulsory Hijab (Case Study: Dusun Baru Pusat Jalo, Muko Muko Bathin VII District, Bungo Regency) and to find out the background to the problem of implementing regulations regarding hijab, the obstacles faced by the Hamlet Government in its implementation and efforts to overcome these obstacles. The method used in this research is a qualitative research method which is a descriptive study. The method used in this research is a qualitative research method which is a descriptive study. The informant selection technique used by researchers in this research was the purposive sampling method (a technique for determining samples with certain considerations). The results of this research indicate that the evaluation of Hamlet Regulation Number 03 of 2020 concerning the Prohibition of Revealing the Private Parts/Compulsory Hijab in the Dusun Baru Pusat Jalo Area, Muko-Muko Bathin VII District is not completely good, this can be seen from: First; Scope. Has been implemented in accordance with the provisions, Second; Prohibition Provisions. There are still people who violate the provisions, especially men who wear shorts. Third; Community Rights and Obligations have been fulfilled properly. Fourth; Penalty. The New Central Jalo Government has implemented warning sanctions or verbal warnings but has not implemented administrative sanctions. The obstacles faced by the Hamlet Government include finding women who do not wear the hijab leaving the house and finding men who wear shorts when leaving the house. Lack of socialization carried out by hamlet officials regarding hamlet regulations regarding the Prohibition of Opening Aurat. There have been no administrative sanctions imposed on people who violate it, even though they have committed several violations